The Frequency of Sharia Supervisory Board Meetings, Profitability, Solvency, and Land Company Size on Audit Report Lag at Islamic Commercial Banks in Indonesia - Umiyati Umiyati; Tuti Novianti; Rahmawati Rahmawati (International Journal of Emerging Issues in Islamic Studies, 2025)
A firm's financial report is the primary source of information that needs to be disclosed on time. However, some Islamic Commercial Banks are still late in reporting audited financial reports, which leads to issues of legitimacy and diminishes public trust in the accuracy and validity of these reports. The primary goal is to analyze the audit report lag and its relationship with the frequency of Sharia Supervisory Board meetings, profitability, solvency, and company size at Islamic Commercial Banks in Indonesia. The audit report lag is measured as the interval of days between the end of the fiscal period and the date of the audit report’s signature. The sample was selected using a purposive sampling technique, comprising 10 Islamic Commercial Banks that published financial reports from 2019 to 2023. The data analysis method used is panel data regression, performed with EViews 13 software. The study finds that the audit report lag for the selected sample ranges from the minimum period of book closing to a maximum of 3 months. The analysis reveals that the frequency of Sharia Supervisory Board meetings, profitability, and company size significantly affect the audit report lag. In contrast, solvency does not have a substantial impact on the audit report lag. Research using the variable of the frequency of Sharia Supervisory Board meetings is still limited. This study brings originality by measuring the influence of the frequency of Sharia Supervisory Board meetings, profitability, solvency, and company size on audit report lag, analyzed through a panel data regression model. To date, no one has conducted this kind of research.